2010
DOI: 10.1002/pd.2507
|View full text |Cite
|
Sign up to set email alerts
|

Postmarital follow‐up survey on high risk patients subjected to premarital screening program in Saudi Arabia

Abstract: This study showed some early benefits of the PMS in prevention of the targeted diseases and the program helped in early detection of the disease in their offspring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 12 publications
4
24
0
Order By: Relevance
“…Alhamdan et al [20] reported a 10.4% at-risk marriage cancellation rate in 2004-2005. Alswaidi and O'Brien [10] reported a rate of 11.8% for 2005-2006 and Al Sulaiman et al [21] reported a rate of 2%, while Memish and Saeedi [1] found a rate of 26.5% in 2004-2009. An increasing at-risk marriage cancellation trend of 9.2% in 2004 to 51.9% in 2009 was found [1].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Alhamdan et al [20] reported a 10.4% at-risk marriage cancellation rate in 2004-2005. Alswaidi and O'Brien [10] reported a rate of 11.8% for 2005-2006 and Al Sulaiman et al [21] reported a rate of 2%, while Memish and Saeedi [1] found a rate of 26.5% in 2004-2009. An increasing at-risk marriage cancellation trend of 9.2% in 2004 to 51.9% in 2009 was found [1].…”
Section: Resultsmentioning
confidence: 99%
“…Bahrain, Iran, Iraqi Kurdistan, Jordan, Saudi Arabia and Turkey) included indicators of programme effectiveness, shown in table 3 [1,4,10,12,13,14,19,20,21,22,23,24,25,26,27]. One source reviewing the United Arab Emirates programme included satisfaction surveys and recommendations but provided no statistics [8].…”
Section: Resultsmentioning
confidence: 99%
“…The reasons for such high rates of those proceeding with their marriage plans, which were also reported following premarital carrier screening programs in Saudi Arabia [21,22], are mainly due to social and cultural obligations and commitments as the premarital screening is performed only a few days prior to the actual legal ceremony. Such a situation would mean that the couple's options to avoid having affected children would be more or less restricted to PND, and also means that PND should be among the priorities of the health authorities to ensure effective prevention.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, consanguineous marriages are widespread within many Saudi communities as traditional practice even though the practice is discouraged by Islam (Alsulaiman, Saeedi, Alsuliman, & Owaidah, 2010). As Modell and Darr (2002) argue in relation to consanguineous marriages; "Although the custom is often perceived to be associated with Islam, in fact itisindependentofreligion" (p. 225).…”
Section: Premarital Screening Programs 24mentioning
confidence: 99%
“…Indeed, concern around the social stigma and family pressure are significant mediators that challenge the cancellation of marriages (Alswaidi et al, 2012). Emotional factors also played a significant role in decision-making regarding high risk marriages, with 98% of incompatible individuals marrying, despite being caught between the opposing forces of love and cultural requirements (Alsulaiman et al, 2010). A newspaper report reflected the public view that traditions and emotion had subjugated the risks associated with marriage between individuals with genetic disorders (Daoud, Albahs, & Alharthi, 2011).…”
Section: Negotiating Reality 73mentioning
confidence: 99%